Exploring Students’ Need for Developing Material of English for Civil Engineering - Arum Nisma Wulanjani (Metathesis: Journal of English Language, Literature, and Teaching, 2018)
Having tailor-made materials for ESP class can really be a hand to achieve learning goals and also to help students to achieve targeted skills and knowledge in ESP class. This study investigated need analysis of Civil Engineering students in a university  in Indonesia in order to explore the needs in developing materials for Civil Engineering students. Need analysis is an important steps in terms of developing materials. In order to detect students’ views toward what they need to learn, their preferred learning style, and their attitudes, interest toward learning English, a revised questionnaire was utilized. There were 61 students involved in this investigation. There was fifteen questions-questionnaire given to the students. An interview was also conducted as triangulation of the data. The results revealed that the students considered that the four macro skills are the most important component ehich neede the most practice, whereas they found grammar as the component that they most resented and had the least expertise in. Moreover, they tended to have various activities when they learn English. They needed various activities to draw their attention and motivation in learning English. It is hoped that the findings from this study can assist teachers and surriculum and syllabus designer to consider the students’ real needs and try to design and develop materials which can fulfill the present gap.